Effect of Rotation Speed on Microstructure and Mechanical Properties of Friction-Stir-Welded 2205 Duplex Stainless Steel - Wenyang Wang; Ye Hu; Tong Wu; Dan Zhao; Hongwei Zhao (Advances in Materials Science and Engineering)
In the present study, 1.86-mm-thick steel plates (UNS S32205) were friction-stir-welded at various rotation speeds of 300 to 600 rpm and a constant welding speed of 100 mm·min−1. The effect of rotation speed on the microstructure and mechanical properties of the welds was researched. The welding temperature was recorded during friction stir welding (FSW), and the microstructure and mechanical properties of the welds were assessed. The incomplete penetration defect was formed at 300 rpm due to the insufficient heat input, and macroscopic groove-like defect was formed at 600 rpm because of the serious sticking of tool. Defect-free welds were obtained at 350 to 500 rpm. The lower rotation speed corresponds to lower heat input during FSW, which resulted in finer recrystallized grains within the stirred zone and thermomechanically affected zone. The joint width was increased with the increasing rotation speed. Therefore, both the strength and hardness of the weld joints increased with the decreasing of rotation speed.